Influence de la variation du taux de sel sur les qualités physicochimiques, microbiologiques et organoleptiques du fromage à pâte molle type camembert à Sidi Saâda - ISSAAD, IBRAHIM; MANKOUR, EL-HADJ (My University, 2017)
The purpose of this study was to determine the possibilities of producing soft cheese Camembert type cheese with high moisture content, with reduced sodium without diminishing, technological and organoleptic qualities of the cheese content. The variation in salt content of our manufacturing tests had effects: A slight increase in the activity of the water without affecting the growth of bacterial and fungal flora contamination. -An action on the TSE, the moisture and weight of samples at the end of ripening rate. -An influence on the evolution of pH, much more marked on items C1 (1,80g NaCl), C2 (2,85g NaCl) and C3 (3,32g NaCl) than the witness, thus neutralizing the acidity the cheese paste was much more pronounced for the less salty than the control and this has influenced the growth of the lactic flora lots. - A very good taste assessment by the panel was noted for the control (5,09g NaCl), although the advantage that the witness